2017
DOI: 10.1111/ecog.03134
|View full text |Cite
|
Sign up to set email alerts
|

On the use of climate covariates in aquatic species distribution models: are we at risk of throwing out the baby with the bath water?

Abstract: Species distribution models (SDMs) in river ecosystems can incorporate climate information by using air temperature and precipitation as surrogate measures of instream conditions or by using independent models of water temperature and hydrology to link climate to instream habitat. The latter approach is preferable but constrained by the logistical burden of developing water temperature and hydrology models. We therefore assessed whether regional scale, freshwater SDM predictions are fundamentally different whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 95 publications
(128 reference statements)
1
33
0
2
Order By: Relevance
“…However, the incorporation of fine-scale biological data into national assessments is not possible due to insufficient data. In addition, incorporating variables that represent instream conditions is recommended to calibrate SDMs for freshwater species, but recent research showed that predictions do not fundamentally differ for climate versus instream-based models (McGarvey et al 2018). Second, despite our efforts to remove any potential sampling biases through careful geographical and environmental filtering of the occurrence records, uneven spatial distribution of collection efforts may have truncated the full range of suitable areas, especially for species for which available data are few and opportunistic (Beck et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the incorporation of fine-scale biological data into national assessments is not possible due to insufficient data. In addition, incorporating variables that represent instream conditions is recommended to calibrate SDMs for freshwater species, but recent research showed that predictions do not fundamentally differ for climate versus instream-based models (McGarvey et al 2018). Second, despite our efforts to remove any potential sampling biases through careful geographical and environmental filtering of the occurrence records, uneven spatial distribution of collection efforts may have truncated the full range of suitable areas, especially for species for which available data are few and opportunistic (Beck et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The accelerating establishment and spread of nonnative species will undoubtedly continue to homogenize China's freshwater fish fauna and further accentuate the loss of distinctiveness across communities in the future (Liu et al 2017a). In addition, incorporating variables that represent instream conditions is recommended to calibrate SDMs for freshwater species, but recent research showed that predictions do not fundamentally differ for climate versus instream-based models (McGarvey et al 2018). This, in turn, could facilitate the establishment of other invaders and exacerbate the magnitude of invasion-related impacts ('invasional meltdown'; sensu Simberloff 2006).…”
Section: Establishment Threat Under Current Scenario (%)mentioning
confidence: 99%
“…The use of such variables for modelling freshwater species may, however, be counterintuitive, given that their distributions are typically limited by instream conditions (e.g., hydrology, water temperature). While high‐resolution instream data are currently unavailable on a global scale, there has been evidence (e.g., McGarvey et al., 2018) demonstrating that climatic variables, in conjunction with physical habitat data, can serve as reasonable surrogates for instream variables, given that these distal variables are often causally linked to proximal drivers of freshwater species distributions (e.g., air temperature directly affecting water temperature; altitude and slope directly influencing channel morphology) (Zeng et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…In brief, SDMs correlate the occurrence of a given species with the environmental conditions, usually climatic, of the sites it inhabits in order to locate areas that are most susceptible to invasion (Guisan and Thuiller 2005). While direct indicators of water conditions (water temperature and river flow) are preferable over indirect climate surrogates (air temperature and precipitation), multiple studies have demonstrated the prominent role of climate over geological (Quinn et al 2014), hydrological (McGarvey et al 2017) or socio-economic aspects (Gallardo and Aldridge 2013a) on the distribution of aquatic organisms at the global scale. Climate surrogates are especially useful when modelling invasive species because they allow using information from the entire global range of distribution of invasive species (native and invasive).…”
Section: Methodsmentioning
confidence: 99%